INTERSEKSI NILAI KULTURAL DAN DISIPLIN MARITIM DALAM MEMBENTUK HABITUS MAHASISWA PELAYARAN - Kurnia, Rahmat; Romadhoni, Dita; David, Muhammad; Agung Kombih, Muhammad; Hasyim Firdaus Siregar, Muhammad; Listiawati, Listiawati (LPPM Universitas Bina Bangsa, 2025)
This study aims to explore how the interaction between the cultural values brought by maritime cadets and the maritime discipline system within educational institutions shapes their habitus during the learning process. Maritime education is characterized by a high level of discipline, strict hierarchy, and the integration of technical skills with strong work ethics and character formation. However, cadets come from diverse cultural backgrounds, carrying values, norms, and social behaviors rooted in their communities. Cultural aspects such as collectivism, attitudes toward authority, and communal responsibility influence their perceptions of institutional rules and discipline. Using a qualitative approach with a case study method at the Malahayati Maritime Polytechnic in Aceh, data were collected through in-depth interviews, participant observation, and document analysis. The findings reveal that the interaction between cultural values and maritime discipline leads to dynamics of adaptation, resistance, and synthesis that form a new habitus. Cadets from collectivist cultures tend to adapt more easily to the hierarchical structure and teamwork, while those from more egalitarian backgrounds are often more critical of authority. Nonetheless, through continuous exposure, practical field experience, and mentorship, most cadets gradually internalize the values of maritime discipline without losing their cultural identity. This study highlights the importance of culturally sensitive curricula and inclusive guidance strategies. The results are expected to contribute to the development of maritime education that not only produces technically competent seafarers but also individuals with strong character, ethics, and the ability to thrive in multicultural working environments.